Peran Tari Zapin dalam Dakwah Islam Di Sumatera Utara - Abdul Gani Jamora Nasution; Adil Rosyadi Hasibuan; Omega Megarani; Ros Suryaningsih Ge'e (Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2022)
The purpose of this study was to find out the role of the zapin dance in Islamic da'wah in North Sumatra. The method used in this study is a qualitative method with data collection techniques of observation, interviews and documentation. The research results obtained are, First, the make-up used in the zapin dance is a realist make-up which functions to emphasize or thicken facial lines and sharpen the expressions of the dance characters being performed. The dress code for the Arabic zapin dance is a symbolic dress code, that is, it has special symbols for a performance that are different from everyday clothes. The clothes used are typical clothes of the Malay tribe. Second, the value of religious education is found in song lyrics, alif worship movements and there are also alif movements that contain the meaning of determination, patience and strength to face all challenges of steadfast life. This is also a religious value where every human being will definitely not escape the problem of being patient and steadfast is the key because patience is part of faith.Third, the zapin dance in Islamic da'wah acts as a means of propaganda through its dance movements which contain Islamic meanings, music which contains the Oneness of Allah and the musical instrument used is the tambourine which is an Islamic musical instrument.